Assessing the impacts of nature-based solutions on ecosystem services: A Water-Energy-Food-Ecosystems nexus approach in the Nima River Sub-Basin (Colombia) - Restrepo, Juan Diego; Bottaro, Giorgia; Barci, Linda; Beltran, Lucila Marcela; Londoño-Behaine, Martin; Masiero, Mauro (MDPI, 2024)
Forest ecosystem services are critical for maintaining ecological balance and supporting human well-being from different perspectives. However, rapid land use changes driven by agricultural expansion, urbanization, and industrial activities have significantly altered forest ecosystems, degrading the services they provide. We here conduct an ecosystem service assessment through biophysical and economic estimates for a multipurpose Andean water sub-basin in western Colombia. We compare a business as usual (BAU) with a forest nature-based solution (NbS) scenario focused on forest landscape restoration. The research employed participatory methods for the NbS selection and economic valuation techniques to evaluate water flow regulation, water provisioning, water purification, and food provisioning services. Results show that the NbS scenario yielded a net positive economic impact across most evaluated ecosystem services, with notable trade-offs. Specifically, the NbS scenario increased water retention by 2.9% compared to BAU. Water flow regulation demonstrated the most substantial economic benefit, increasing by EUR 11.39 million/year in the NbS scenario. On the other hand, the food provisioning service presented a reduction of EUR 3.2 million/year in the NbS scenario. These findings highlight the potential of forest-based NbS to address the Water–Energy–Food–Ecosystem (WEFE) nexus challenges. The study’s outcomes provide valuable insights for policymakers and practitioners, supporting the development of Payment for Ecosystem Services schemes and integrating ecosystem service valuation into land use planning and decision-making processes.